AI-Attas's islamic conceptions Of happiness : revisiting the Malay hero Hang Tuah. - Hamdan, Rahimah; Md. Radzi, Shaiful Bahri (2013)
Hang Tuah as Malay elite hero has been portrayed as a man that solely put his loyalty to his king. The term is precisely described the view of the ancient people during that era that assume the king as a 'Khalifah di bumi". Thus when Malacca has been defeated by the Portuguese in the 1511, there were chaos in the heart, mind and souls of the Malays people due to the faIl of this great empire. Therefore, in the 18th century the Hikayat Hang Tuah has been written to empowering the nationalism and patriotic spirits of the Malays people. Hang Tuah's character signifies the Malay- Islamic heroes that reunite the people that lost their faith during that era. However, when examining the Hikayat Hang Tuah, it was found that the Malay battle is based on the nation and not the Islam religion that should be the main core. It is portrayed as the fight without souls when the religion belief is not included from the beginning. Therefore, this paper will examine the happiness elements seek by Hang Tuah as the Islamic Malay hero and identify whether that is the happiness that his seek for? Based on happiness perspective of Syed Naquib al-Attas (ukhrawiyyah dan dunyawiyyah ), this research wiIl analyze the "Happiness" of Hang Tuah as Malay hero and its relevance as Malay hero in today's generation.